Anisotropy in the transport properties of type II superconducting films with periodic pinning - Verga, L. G. [UNESP]; Da Silva, M. C. [UNESP]; Simões, R. P. [UNESP]; Mello, Denise Fernandes de [UNESP]; Venegas, Pablo Antonio [UNESP] (Springer Nature, 2013)
Using numerical simulations, we analyze the anisotropy effects in the critical currents and dynamical properties of vortices in a thin superconducting film submitted to hexagonal and Kagomé periodical pinning arrays. The calculations are performed at zero temperature, for transport currents parallel and perpendicular to the main axis of the lattice, and parallel to the diagonal axis of the rhombic unit cell. We show that the critical currents and dynamic properties are anisotropic for both pinning arrays and all directions of the transport current. The anisotropic effects are more significant just above the critical current and disappear with higher values of current and both pinning arrays. The dynamical phases for each case and a wide range of transport forces are analyzed. © 2012 Springer Science+Business Media, LLC.
Keywords: Critical currents; Periodic pinning; Superconductivity; Vortex dynamics; Anisotropic effects; Anisotropy effect; Dynamical properties; Thin superconducting films; Transport currents; Zero temperatures; Superconducting films; Transport properties; Vortex flow; Anisotropy